Variability of Tropical Cyclone Frequency Over the Western North Pacific in 2018–2020 - Ogata, Tomomichi; Baba, Yuya (Frontiers in Climate, 2021)
In this study, we examine the tropical cyclone (TC) activity over the western North Pacific (WNP) in 2018–2020 and its relationship with planetary scale convection and circulation anomalies, which play an important role for TC genesis. To determine the sea surface temperature (SST)-forced atmospheric variability, atmospheric general circulation model (AGCM) ensemble simulations are executed along with the observed SST. For AGCM experiments, we use two different convection schemes to examine uncertainty in convective parameterization and robustness of simulated atmospheric response. The observed TC activity and genesis potential demonstrated consistent features. In our AGCM ensemble simulations, the updated convection scheme improves the simulation ability of observed genesis potential as well as planetary scale convection and circulation features, e.g., in September–October–November (SON), a considerable increase in the genesis potential index over the WNP in SON 2018, WNP in SON 2019, and South China Sea (SCS) in SON 2020, which were not captured in the Emanuel scheme, have been simulated in the updated convection scheme.